A High‐Throughput Automated Confocal Microscopy Platform for Quantitative Phenotyping of Nanoparticle Uptake and Transport in Spheroids. Issue 37 (23rd July 2019) - Cutrona, Meritxell B.; Simpson, Jeremy C.
Abstract: There is a high demand for advanced, image‐based, automated high‐content screening (HCS) approaches to facilitate phenotypic screening in 3D cell culture models. A major challenge lies in retaining the resolution of fine cellular detail but at the same time imaging multicellular structures at a large scale. In this study, a confocal microscopy‐based HCS platform in optical multiwell plates that enables the quantitative morphological profiling of populations of nonuniform spheroids obtained from HT‐29 human colorectal cancer cells is described. This platform is then utilized to demonstrate a quantitative dissection of the penetration of synthetic nanoparticles (NP) in multicellular 3D spheroids at multiple levels of scale. A pilot RNA interference‐based screening validates this methodology and identifies a subset of RAB GTPases that regulate NP trafficking in these spheroids. This technology is suitable for high‐content phenotyping in 3D cell‐based screening, providing a framework for nanomedicine drug development as applied to translational oncology. Abstract : This study describes a quantitative imaging approach for dissecting how nanomaterials interact with and traffic in cells growing in three dimensions. The approach combines several unique aspects of experimental design, imaging, and image analysis enabling acquisition of high‐resolution images of several hundred spheroids per well in multiwell plates, in turn facilitating the quantitative analysis of nanoparticle trafficking at the subcellular scale.